2009
DOI: 10.1111/j.1439-0396.2008.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β‐glucanase and xylanase supplementation on gastrointestinal digestive enzyme activities of weaned piglets fed a barley‐based diet

Abstract: The effects of supplementing a barley-based diet for weaned piglets withexogenous beta-glucanase and xylanase on gastrointestinal digestiveenzyme activities were investigated. Thirty-six cross-bred weaned pigletswere randomly assigned to two groups with three pens based on sexand mass. Each group was fed on the diet based on barley with or withoutadded beta-glucanase and xylanase (0.15%) for a 4-week period. Theresults showed that enzyme supplementation improved growth performanceof piglets significantly (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…Similar to present study, EO and XB supplementation did not improve ADG in piglets fed wheat barley-based diets (Muhl and Liebert, 2007;Owusu-Asiedu et al, 2010). In contrast, increased growth performance was reported by other authors (Fan et al, 2009;Maenner et al, 2011). The obtained results on growth performance could outline that the positive effects over the gut environment and inflammatory mediators or microbial faecal counts lead to a better health status of the piglets, but the effects of the administered compounds over these parameters was not sufficient to translate in increased growth.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Similar to present study, EO and XB supplementation did not improve ADG in piglets fed wheat barley-based diets (Muhl and Liebert, 2007;Owusu-Asiedu et al, 2010). In contrast, increased growth performance was reported by other authors (Fan et al, 2009;Maenner et al, 2011). The obtained results on growth performance could outline that the positive effects over the gut environment and inflammatory mediators or microbial faecal counts lead to a better health status of the piglets, but the effects of the administered compounds over these parameters was not sufficient to translate in increased growth.…”
Section: Discussionsupporting
confidence: 58%
“…Enzymes may improve gut health through the production of a variety of polysaccharide hydrolysis products that manipulate the growth of gastrointestinal microorganisms and/or reducing the intestinal viscosity due to the soluble non-starch polysaccharide, which might reduce rate of digesta passage and diffusion of digestive enzymes (de Lange et al, 2010). Fan et al (2009) evidenced an increase of the villus height in the duodenum, jejunum and ileum and decreased crypt depth in response to dietary supplementation of Acanthopanax senticosus extract, and Mathlouthi et al (2002) found that the addition of XB increased the villus size and V : C ratio of broilers. Despite the positive results obtained over intestinal histometry in treated animals, in the present study no enhanced faecal nutrients digestibility was observed, possibly because the observational period of the present study was that one around weaning, a period notoriously rich in stressful events which tend to diminish performances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged accumulation of undigested material in the gut could cause an increase in size of gastrointestinal tract and organs as a response to intestinal motility and digestive excretions (Shakouri, Iji, Mikkelson, & Cowieson, 2009). The increase in pancreas weight for birds fed barley could be related to an increase in endogenous enzyme activities and secretion volume required to digest barley, as reported earlier by Fan, Han, Xu, Wang, & Shi (2008). The reduction in the size and weight of the intestine and pancreas is related to the decrease of digesta viscosity and rapid digestion of nutrients (Wang, Qiao, Lu, and Li, 2005).…”
Section: Carcass Characteristics and Gastrointestinal Parameterssupporting
confidence: 59%
“…The most of the studies focuses on the use of exogenous NSP enzymes in diets for weaned piglets, as especially piglets do not produce enzymes capable of degrading NSP (Kerr & Shurson 2013). Li et al (2004) and Fan et al (2009) reported that the addition of b-glucanase and xylanase to barley-based diets improved growth performance of piglets. However, the need for exogenous NSP enzyme supplementation of barley-based diets on weaned piglets can depend on the used barley variety (Prandini et al 2014).…”
Section: Discussionmentioning
confidence: 99%